Study of pure and mixed clustered noble gas puffs irradiated with a high intensity (7 × 1019 W/cm2) sub-ps laser beam and achievement of a strong X-ray flash in a laser-generated debris-free X-ray source. (22nd July 2019) - Schultz, K. A.; Kantsyrev, V. L.; Safronova, A. S.; Shlyaptseva, V. V.; Petkov, E. E.; Shrestha, I. K.; Cooper, M. C.; Petrov, G. M.; Stafford, A.; Butcher, C. J.; Kemp, G. E.; Park, J.; et al.
Abstract: We present a broad study of linear, clustered, noble gas puffs irradiated with the frequency doubled (527 nm) Titan laser at Lawrence Livermore National Laboratory. Pure Ar, Kr, and Xe clustered gas puffs, as well as two mixed-gas puffs consisting of KrAr and XeKrAr gases, make up the targets. Characterization experiments to determine gas-puff density show that varying the experimental parameter gas-delay timing (the delay between gas puff initialization and laser-gas-puff interaction) provides a simple control over the gas-puff density. X-ray emission (>1.4 keV) is studied as a function of gas composition, density, and delay timing. Xe gas puffs produce the strongest peak radiation in the several keV spectral region. The emitted radiation was found to be anisotropic, with smaller X-ray flux observed in the direction perpendicular to both laser beam propagation and polarization directions. The degree of anisotropy is independent of gas target type but increases with photon energy. X-ray spectroscopic measurements estimate plasma parameters and highlight their difference with previous studies. Electron beams with energy in excess of 72 keV are present in the noble gas-puff plasmas and results indicate that Ar plays a key role in their production. A drastic increase in harder X-ray emissions (X-ray flash effect) and multi-MeV electron-beam generation from Xe gas-puff plasma occurred when the laser beam was focused on the front edge of the linear gas puff.